Website usability testing of Corporate Fund “University Medical Center”: neuromarketing approach - Orazgaliyeva, E.B.; Kazybayeva, A.M.; Smykova, M.R. (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of the study is to identify the weaknesses of the “University Medical Center” website using both traditional marketing and innovative marketing techniques, including neuromarketing technologies. This will enable us to understand the extent to which the neuromarketing approach requires fewer financial resources. The conclusions and recommendations drawn from the study will provide the necessary information to enhance the functionality of the “University Medical Center” website. Methods: As a methodology in the usability testing study, a neuromarketing approach and a questionnaire were used. The Eye Tracking technology and the iMotions program were used in the research. Also, a questionnaire was compiled, which was conducted with respondents before and after the Eye Tracking analysis. Findings: Based on the experience gained during this research work, it can be concluded that the use of a mixed approach to marketing research is very effective. This method is more accurate than traditional research, but cheaper than neuromarketing. Conclusions: At the end of the study, it was concluded that innovative marketing, namely the use of a neuromarketing approach, requires fewer financial resources. Based on the results of the research, recommendations were formulated for positioning the Corporate Fund “University Medical Center” and recommendations for the website based on the research.